ASSESSMENT OF PROBIOTIC PROPERTIES OF THE STRAIN LACTOBACILLUS PARACASEI D6 AND ITS ANTICANDIDAL ACTIVITIES - SAIKIA, DEVABRATA; MANDAL, MANABENDRA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the study was to determine the probiotic properties of a strain Lactobacillus paracasei D6 (GenBank Accession No. KJ867173) and to assess its antifungal activities against certain Candida strains. Methods: Antifungal activities of Lactobacillus paracasei D6 was tested against Candida tropicalis BSS7 and C. albicans MTCC 3017. The cell-free extract was tested against the formation of biofilm and germ tube of the aforementioned Candida strains. Different probiotic activities such as tolerance to simulated gastrointestinal fluid, adhesion to hydrocarbons, and Caco-2 cell line were evaluated for the strain Lactobacillus paracasei D6. Inhibition of Candida strains to Caco-2 cell line was also tested. The strains were identified using gene sequencing followed by phylogenetic tree construction. Results: The probiotic properties of Lactobacillus paracasei D6 were found to be statistically comparable with a standard Lactobacillus plantarum MTCC 1407. The biofilm and germ tube formation patterns of the food spoilage isolate C. tropicalis BSS7 were found to be similar to the strain C. albicans MTCC 3017. Cell-free extract of Lactobacillus paracasei D6 exhibited minimum biofilm inhibitory concentration of 0.438 mg/ml against C. tropicalis BSS7, which was found to be sufficient to inhibit its germ tube formation. The adhesion of C. tropicalis BSS7 to the epithelial Caco-2 cell line was also significantly reduced by the antifungal metabolites. Conclusion: This work gives insight on possible virulent nature of the food isolate C. tropicalis BSS7. Exometabolites produced by L. paracasei D6 were able to inhibit growth, biofilm and germ tube formation of both the strains. With this work, the authors envisage the beginning of an alternative strategy for anticandidal therapy.